Salivary alpha-amylase and tooth pulp evoked potentials in paroxysmal trigeminal neuralgia patients - Vuković, Branislava; Lazić, Zoran; Nikolić, Živorad; Kolar, Jovo; Avramov, Stevan; Cenić-Milošević, Desanka (Vojnosanitetski pregled, 2021)
Background/Aim. The sudden and excruciating pain that characterizes paroxysmal trigeminal neuralgia (PTN) has a negative effect on the wellbeing of the affected individuals, causing psychological distress. Salivary alpha-amylase (sAA) level represents an objective assessment of physical, physiological, and psychological stress. Evoked potentials (EPs) reflect nerve function and evaluate a functional aspect of the trigeminal nerve conduction. The aim of this study was to analyze possible modifications in painful impulses conduction related to sAA level by registering tooth pulp EPs in PTN patients. Methods. The study included ten PTN patients and twelve healthy subjects. The activity of sAA was measured using the Nipro Salivary Amylase Monitor. In order to record EPs response, the dental pulp of vital teeth was electrically stimulated through intact enamel. For stimulation and impulse registration, we used Xltek Protektor 32 system, software EPWorks, version 5.0. Results. The results obtained in PTN patients showed a higher number of waves and significantly shorter latencies and lower amplitudes N2-P2 and N3-P3 at the neuralgic side compared to the healthy side of the same patient, as well as to the controls (p < 0.05). Moreover, latencies were significantly shorter in patients with higher sAA levels than in those with normal sAA levels (p < 0.05). Late latencies (N2 and P2) at the healthy side in patients with higher sAA levels were significantly shorter compared to patients whose sAA levels were normal (p < 0.05). Conclusion. This study showed that psychical stress associated with PTN probably further increased hyperexcitability and conduction velocity of the affected nerves. Moreover, it seems that anticipation of stressful pain even increases the conduction velocity of unaffected nerves at the thalamocortical level in PTN patients. However, in healthy individuals, stress itself had no influence on painful impulses conduction.